Manajemen Pondok Berbasis Karakter Pendidikan Agama Islam : (Studi Kasus Di Pendidikan Pada Kesetaraan Pondok Pesantren Salafiyah (PKPPS) Miftachul Ulum) - Satunggale Kurniawan; Muhammad Afifi Rahman; Yuventius Sugiarno (Jurnal Pendidikan Educandum, 2025)
One of the environments that allows the formation of professional attitudes in students is the boarding school. In the boarding school, students will be introduced to the habits and noble values ​​related to the profession they want to form. Through the regulations that are prepared and implemented by and for themselves and under the guidance of the caregivers, they will know, internalize, and ultimately practice these values ​​later when they enter society. Considering how important the role of the boarding school is, especially in forming attitudes for students, the boarding school needs to be planned, organized and evaluated continuously by involving the boarding school personnel under the coordination of the head of the boarding school. Based on the description above, the focus of this study is the motivation of Educators in learning the boarding school model based on character and Islamic Religious Education, as well as the planning of the boarding school based on character and Islamic Religious Education, and the strategy for implementing character building values ​​in the boarding school based on Islamic Religious Education. therefore to see How is the motivation of Educators in learning the character-based dormitory model and Islamic Religious Education in Education at the Salafiyah Islamic Boarding School Equivalency (PKPPS) Miftachul Ulum, and How is the planning of the character-based dormitory and Islamic Religious Education and How is the strategy for implementing character building values ​​in the Islamic Religious Education-based dormitory in the Islamic boarding school.